The achievement of ligand-functionalized organic/polymeric nanoparticles for treating multidrug resistant cancer. (3rd August 2017) - Lee, Wing-Hin; Loo, Ching-Yee; Leong, Chean-Ring; Young, Paul M.; Traini, Daniela; Rohanizadeh, Ramin
ABSTRACT: Introduction : The effectiveness of conventional cancer chemotherapy is hampered by the occurrence of multidrug resistance (MDR) in tumor cells. Although many studies have reported the development of novel MDR chemotherapeutic agents, clinical success is lacking owing to the high associated toxicity. Nanoparticle-based delivery of chemotherapeutic drugs has emerged as alternative approach to treat MDR cancers via exploitation of leaky vasculature in the tumor microenvironment. Accordingly, functionalization of nanoparticles with target specific ligands can be employed to achieve significant improvements in the treatment of MDR cancer. Areas covered : This review focuses on the recent advances in the functionalization of nanocarriers with specific ligands, including antibodies, transferrin, folate, and peptides to overcome MDR cancer. The limitations of effective ligand-functionalized nanoparticles as well as therapeutic successes in ligand targeting are covered in the review. Expert opinion : Targeting MDR tumors with ligand-functionalized nanoparticles is a promising approach to improve the treatment of cancer. With this approach, higher drug concentrations at targeted sites would be achieved with lower dosage frequencies and reduced side effects in comparison to existing formulations of chemotherapeutic drugs. However, potential toxicities and immunological responses to ligands should be carefully reviewed for viable options in for future MDR cancer treatment.